ANALISIS MISKONSEPSI LITERASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL PISA DITINJAU DARI METAKOGNISI & GENDER - Mira Rahmawati; Nani Ratnaningsih; Sri Tirto Madawistama (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aimed to analyze students' misconceptions of mathematical literacy in solving PISA questions in terms of metacognition and gender. This research is qualitative exploratory research with the topics presented are related to PISA questions. Data collection techniques began with the provision of metacognition questionnaires, PISA mathematical literacy questions and interviews. The subjects of this study were students of class XI SMAN 1 Pamarican who were selected purposively. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. In this study, the focus of research is the misconception of students' mathematical literacy according to 6 levels of mathematical literacy competence in solving PISA questions in terms of metacognition classified based on metacognition (low), and a review of gender (male and female). The results showed that the misconception of metacognition classification was not good enough for men to have misconceptions at level 2, while women experienced a misconception of strategies at level 1. In addition, men and women were caused by wrong intuition. The solution for boys is that students do not think this problem is easy. The information that already known and written checked again, whether used or not and the calculation operation is correct. Meanwhile, the solution for women is to identify the sentence in the problem and start thinking using simple mathematical calculation formulas, such as performing mathematical arithmetic operations.